Insights into the Role of Natural Products in the Control of the Honey Bee Gut Parasite (Nosema spp.) - Hesham R. El-Seedi; Aida A. Abd El-Wahed; Yahya Al Naggar; Aamer Saeed; Jianbo Xiao; Hammad Ullah; Syed G. Musharraf; Mohammad H. Boskabady; Wei Cao; Zhiming Guo; Maria Daglia; Abeer El Wakil; et al. (Animals, 2022)
The honey bee is an important economic insect due to its role in pollinating many agricultural plants. Unfortunately, bees are susceptible to many pathogens, including pests, parasites, bacteria, and viruses, most of which exert a destructive impact on thousands of colonies. The occurrence of resistance to the therapeutic substances used against these organisms is rising, and the residue from these chemicals may accumulate in honey bee products, subsequently affecting the human health. There is current advice to avoid the use of antibiotics, antifungals, antivirals, and other drugs in bees, and therefore, it is necessary to develop alternative strategies for the treatment of bee diseases. In this context, the impact of nosema diseases (nosemosis) on bee health and the negative insults of existing drugs are discussed. Moreover, attempts to combat nosema through the use of alternative compounds, including essential oils, plant extracts, and microbes in vitro and in vivo, are documented.